2018
DOI: 10.1176/appi.ps.201700472
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Assessed Fidelity and Self-Reported Employment in the Individual Placement and Support Model of Supported Employment

Abstract: Higher-fidelity implementation of the IPS model, as self-assessed by program sites, was associated with higher employment rates, which were sustained over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Results from this pilot study and others (Margolies et al 2017(Margolies et al , 2018 suggest that intermediary organizations may be positioned to provide expert training and technical assistance to help programs integrate self-assessments with quality improvement activities. Programs that learn to conduct self-assessment and use the results to implement and sustain practice may demonstrate greater buy-in as they take ownership of the ongoing process.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Results from this pilot study and others (Margolies et al 2017(Margolies et al , 2018 suggest that intermediary organizations may be positioned to provide expert training and technical assistance to help programs integrate self-assessments with quality improvement activities. Programs that learn to conduct self-assessment and use the results to implement and sustain practice may demonstrate greater buy-in as they take ownership of the ongoing process.…”
Section: Discussionmentioning
confidence: 76%
“…This pilot, including eleven programs, found that self-assessment and independent fidelity ratings did not differ significantly from one another (Margolies et al 2017). Further, there was a significant positive relationship between self-reported fidelity and employment that was sustained for a year (Margolies et al 2018).…”
mentioning
confidence: 85%
“…The first was the use of a randomized controlled design. As described in a review of (21,22), a stronger focus on aligning the current study with best practices may have rendered higher rates of employment. Additionally, the population served had low rates of psychotic disorders, resulting in limitations to generalizability.…”
Section: Discussionmentioning
confidence: 96%
“…While self-assessment might lead to bias under certain conditions (e.g., when licensing depends upon proving model fidelity), there is some emerging evidence that, when supported as part of a quality-improvement process without penalty, self-assessment and independent fidelity ratings do not differ significantly from one another (Covell et al, 2021a , b ; Margolies et al, 2017 ). Further, one study demonstrated a significant positive relationship between self-reported fidelity and outcomes (employment) that was sustained for a year (Margolies et al, 2018 ). Third, the agency described herein is a large well-resourced agency.…”
Section: Discussionmentioning
confidence: 99%